Lec 15

# Lec 15 - UCLA Spring 2009-2010 Systems and Signals Lecture...

This preview shows pages 1–9. Sign up to view the full content.

UCLA Spring 2009-2010 Systems and Signals Lecture 15: Inversion of the Laplace Transform May 19, 2010 EE102: Systems and Signals; Spr 09-10, Lee 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Inversion of the Laplace transform From Lecture 14, the inverse Laplace transform is given by f ( t ) = 1 2 πj Z c + j c - j F ( s ) e st ds where σ is large enough that F ( s ) is deﬁned for < s c This involves a contour integral in the complex plane. Simpler approach: rewrite a rational Laplace transform into simple terms we recognize, and can invert by inspection ( partial fraction expansion ). Computationally the same operations as contour integral. EE102: Systems and Signals; Spr 09-10, Lee 2
Partial fraction expansion F ( s ) = b ( s ) a ( s ) = b 0 + b 1 s + ··· + b m s m a 0 + a 1 s + ··· + a n s n Let’s assume (for now) no poles are repeated, i.e. , all roots of a have multiplicity one m < n then we can write F in the form F ( s ) = r 1 s - λ 1 + ··· + r n s - λ n called partial fraction expansion of F EE102: Systems and Signals; Spr 09-10, Lee 3

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
λ 1 ,...,λ n are the poles of F the numbers r 1 ,...,r n are called the residues when λ k = λ * l , r k = r * l Example: s 2 - 2 s 3 + 3 s 2 + 2 s = - 1 s + 1 s + 1 + 1 s + 2 Let’s check: - 1 s + 1 s + 1 + 1 s + 2 = - 1( s + 1)( s + 2) + s ( s + 2) + s ( s + 1) s ( s + 1)( s + 2) In partial fraction form, inverse Laplace transform is easy: L - 1 [ F ( s )] = L - 1 ± r 1 s - λ 1 + ··· + r n s - λ n ² EE102: Systems and Signals; Spr 09-10, Lee 4
= r 1 L - 1 ± 1 s - λ 1 ² + ··· + r n L - 1 ± 1 s - λ n ² = r 1 e λ 1 t + ··· + r n e λ n t This is real since whenever the poles are conjugates, the corresponding residues are also. EE102: Systems and Signals; Spr 09-10, Lee 5

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Finding the partial fraction expansion Two steps: ﬁnd poles λ 1 ,...,λ n ( i.e. , factor a ( s ) ) ﬁnd residues r 1 ,...,r n (several methods) Method 1: Clear Fractions, Solve linear equations We’ll illustrate for m = 2 , n = 3 b 0 + b 1 s + b 2 s 2 ( s - λ 1 )( s - λ 2 )( s - λ 3 ) = r 1 s - λ 1 + r 2 s - λ 2 + r 3 s - λ 3 Clear denominators: b 0 + b 1 s + b 2 s 2 = r 1 ( s - λ 2 )( s - λ 3 )+ r 2 ( s - λ 1 )( s - λ 3 )+ r 3 ( s - λ 1 )( s - λ 2 ) EE102: Systems and Signals; Spr 09-10, Lee 6
Equate coeﬃcients: coeﬃcient of s 0 : b 0 = ( λ 2 λ 3 ) r 1 + ( λ 1 λ 3 ) r 2 + ( λ 1 λ 2 ) r 3 coeﬃcient of s 1 : b 1 = ( - λ 2 - λ 3 ) r 1 + ( - λ 1 - λ 3 ) r 2 + ( - λ 1 - λ 2 ) r 3 coeﬃcient of s 2 : b 2 = r 1 + r 2 + r 3 Now solve for r 1 ,r 2 ,r 3 (three equations in three variables) EE102: Systems and Signals; Spr 09-10, Lee 7

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
To get r 1 , multiply both sides by s - λ 1 to get ( s - λ 1 )( b 0 + b 1 s + b 2 s 2 ) ( s - λ 1 )( s - λ 2 )( s - λ 3 ) = r 1 + r 2 ( s - λ 1 ) s - λ 2 + r 3 ( s - λ 1 ) s - λ 3 cancel s - λ 1 term on left and set s = λ 1 : b 0 + b 1 λ 1 + b 2 λ 2 1 ( λ 1 - λ 2 )( λ 1 - λ 3 ) = r 1 an explicit formula for r 1 ! We can get
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 10/21/2010 for the course EE ee102 taught by Professor Levan during the Spring '09 term at UCLA.

### Page1 / 34

Lec 15 - UCLA Spring 2009-2010 Systems and Signals Lecture...

This preview shows document pages 1 - 9. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online